2021
DOI: 10.1088/1361-6528/abf458
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained molecular simulation of the effects of carbon nanotube dispersion on the mechanics of semicrystalline polymer nanocomposites

Abstract: With the incorporation of carbon nanotubes (CNTs), CNT/polypropylene (PP) nanocomposites are found to possess enhanced mechanical properties, but the reinforcing effect is reduced at large added CNT weight percentages due to CNT aggregation. Optimizing the properties of a nanocomposite requires a fundamental understanding of the effects of CNT dispersion on the nanocomposite. In this work, coarse-grained molecular models of CNT/PP nanocomposites are constructed, which consist of randomly dispersed or aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 77 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Recent studies use even coarser schemes, choosing a Kuhn monomer to represent a bead. 30,31 The challenge in polypropylene coarse-graining is connected to its structure. Specifically, polypropylene is a branched vinyl polymer which exhibits a tendency to form helices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies use even coarser schemes, choosing a Kuhn monomer to represent a bead. 30,31 The challenge in polypropylene coarse-graining is connected to its structure. Specifically, polypropylene is a branched vinyl polymer which exhibits a tendency to form helices.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the strong Van der Waals forces, CNTs are easy to aggregate and difficult to be uniformly dispersed in the matrix 26 . In our previous work, we have reported a hybrid where CNTs grow directly on the surface of fibers, which has been a promising method to improve the CNT dispersion in the matrix 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…In the conductive fillers, CNTs have been widely applied in the EM wave absorbing materials because of their high conductivity and compatibility with polymer matrix 24,25 . However, due to the strong Van der Waals forces, CNTs are easy to aggregate and difficult to be uniformly dispersed in the matrix 26 . In our previous work, we have reported a hybrid where CNTs grow directly on the surface of fibers, which has been a promising method to improve the CNT dispersion in the matrix 27,28 …”
Section: Introductionmentioning
confidence: 99%
“…The enhancements reported thus far are much lower than or inconsistent with the theoretical predictions. For example, it is observed from experiments that CNTs/polypropylene composites exhibit the highest mechanical properties at 0.5–1.0 wt % CNT, while the atomistic simulation predicted that Young’s modulus gradually increases with CNTs’ content up to 9.0 wt % …”
Section: Introductionmentioning
confidence: 99%
“…Previous works suggest that a uniform dispersion is the key to minimize the presence of stress concentration and achieve efficient load transfer between the nanofiller and polymer matrix. Researchers found that a poor dispersion results in severe aggregation at a relatively large CNT content (e.g., 5.0 wt % of CNTs in polypropylene , ), which leads to a lower yield strength, hardness, and indentation modulus. Therefore, continuing efforts have been devoted to improve the dispersion of CNTs, such as the usage of physical treatment, electrostatic treatment, , and surfactants .…”
Section: Introductionmentioning
confidence: 99%